An analysis of the Participation Motivation of Marathon Runners in Nanchang - 肖, 城 (Pacific International Journal, 2023)
The aim of this paper is to investigate the participation motivation of marathon runners in Nanchang City. The study utilizes a literature review method, questionnaire method, and mathematical and statistical analysis to explore the topic in detail among the public in Nanchang City. After analyzing the data on participants' sports motivation and influence, the study finds that the participation in marathons among Nanchang City residents needs to be enhanced, as the participation time is insufficient and public sports values need to be corrected. The study suggests enhancing the participation motivation of marathon runners in Nanchang, improving the awareness of scientific exercise among participants, and developing correct sporting values. Additionally, it is necessary to promote the development of marathons in Nanchang by enhancing participation, self-confidence, theoretical guidance, and analysis of the scientific basis for the promotion of the sport. This study provides active academic references for public participation in physical fitness activities in Nanchang City.